PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, PELUANG PERTUMBUHAN TERHADAP KEBIJAKAN DIVIDEN - Vania Vania; Ardiansyah Ardiansyah (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study is to determine whether profitability, growth opportunities, company size, and leverage have an influence on dividend policy. This study use purposive sampling method and use 40 manufacturing companies listed on the Indonesia Stock Exchange during 2016-2019. This study use multiple regression analysis with eviews 12. The results show that company size and leverage do not have a significant effect on dividend policy, while growth opportunities and profitability have a significant positive effect on dividend policy. The implication of this research is companies need to increase their profits, so that companies are able to distribute dividends in high amounts and attract investorattention.